2011
DOI: 10.1016/j.jcomdis.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Emotional reactivity, regulation and childhood stuttering: A behavioral and electrophysiological study

Abstract: The purpose of this preliminary study was to assess whether behavioral and psychophysiological correlates of emotional reactivity and regulation are associated with developmental stuttering, as well as determine the feasibility of these methods in preschool-age children. Nine preschool-age children who stutter (CWS) and nine preschool-age children who do not stutter (CWNS) listened to brief background conversations conveying happy, neutral, and angry emotions (a resolution conversation followed the angry conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
111
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 84 publications
(126 citation statements)
references
References 83 publications
(107 reference statements)
13
111
1
1
Order By: Relevance
“…Kochanska, Aksan, Penney, & Doobay, 2007, who reported that low-arousal positive affect [e.g., agreeableness or affiliation] was associated with enhanced effortful control 6 ). It might be speculated that young CWS's relatively high Surgency with relatively low emotion regulation is related to disruptions in their speech fluency, the latter speculation consistent with the findings reported by Arnold et al (2011). It is of interest that Kagan (2012) suggested that children who are high positive (i.e., more surgent) as infants " retained their profile of high sociability and low timidity through school entrance because these child behaviors are not subject to disapproval by adults and peers" (p. 73).…”
Section: Impact Of Endogenous Emotional Diathesis On Stutteringsupporting
confidence: 83%
See 3 more Smart Citations
“…Kochanska, Aksan, Penney, & Doobay, 2007, who reported that low-arousal positive affect [e.g., agreeableness or affiliation] was associated with enhanced effortful control 6 ). It might be speculated that young CWS's relatively high Surgency with relatively low emotion regulation is related to disruptions in their speech fluency, the latter speculation consistent with the findings reported by Arnold et al (2011). It is of interest that Kagan (2012) suggested that children who are high positive (i.e., more surgent) as infants " retained their profile of high sociability and low timidity through school entrance because these child behaviors are not subject to disapproval by adults and peers" (p. 73).…”
Section: Impact Of Endogenous Emotional Diathesis On Stutteringsupporting
confidence: 83%
“…Caregivers were informed of the study via (a) a free, widely read, regionally distributed parent-oriented magazine, (b) local health care provider, or (c) self-or professional referral to the Vanderbilt Developmental Stuttering Laboratory. Participants were part of an ongoing series of empirical investigations of linguistic and emotional contributors to developmental stuttering (e.g., Arnold et al, 2011;Clark, Conture, Frankel, & Walden, 2012;Clark, Conture, Walden, & Lambert, 2013K. Johnson et al, 2010;Jones, Buhr, et al, 2014;Ntourou et al, 2013;Tumanova, Conture, Lambert, & Walden, 2014;Zengin-Bolatkale, Conture, & Walden, 2015) conducted by the Vanderbilt University Developmental Stuttering Project.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were previously collected as part of an ongoing series of empirical investigations of linguistic and emotional associates of childhood stuttering conducted by Vanderbilt University's Developmental Stuttering Project (e.g., Arnold, Conture, Key, & Walden, 2011;Choi, Conture, Walden, Lambert, & Tumanova, 2013;Clark, Conture, Frankel, & Walden, 2012;Johnson, Walden, Conture, & Karrass, 2010;Jones et al, 2014;Millager et al, 2014;Richels et al, 2010;Walden et al, 2012). Children were paid volunteers whose caregivers learned of the study from (a) a free monthly parent magazine circulated throughout middle Tennessee, (b) a local health care provider, or (c) self-or professional referral to the Vanderbilt Bill Wilkerson Hearing and Speech Center for an evaluation.…”
Section: Participantsmentioning
confidence: 99%